2019
DOI: 10.1108/ijse-04-2018-0168
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous specification of foreign capital inflows, human capital development and economic growth

Abstract: Purpose The purpose of this paper is to empirically investigate the relationship between foreign capital inflows, human capital development (HCD) and economic growth in ECOWAS countries. Design/methodology/approach In line with the augmented Solow model, the relationship between foreign capital inflows, human capital development and gross domestic product in the ECOWAS member countries is investigated using the pool mean group method. Findings The authors find overwhelming evidence that foreign capital inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 53 publications
3
36
1
2
Order By: Relevance
“…This negative effect can be due to the fungible nature of most official development aid flowing into the sub region. This outcome confirms the findings of Musibau et al (2019) and contradicts Juselius et al (2014). On the other hand and in line with the findings of Bird and Choi (2020) FDI is positive and statistically significant at 5% for all the four models employed.…”
Section: Short and Long Run Dynamicssupporting
confidence: 89%
See 1 more Smart Citation
“…This negative effect can be due to the fungible nature of most official development aid flowing into the sub region. This outcome confirms the findings of Musibau et al (2019) and contradicts Juselius et al (2014). On the other hand and in line with the findings of Bird and Choi (2020) FDI is positive and statistically significant at 5% for all the four models employed.…”
Section: Short and Long Run Dynamicssupporting
confidence: 89%
“…With the global village nature of the world today, where shock in one country affect other countries, economic analyses have tend to adopt more robust methodologies that account for cross country dependence. Most existing studies in this domain have mainly used conventional estimation techniques like FE, RE and GMM (Bird & Choi, 2020;Karagoz & Caglar, 2016), Pooled mean group (PMG) and panel VAR (Guei, 2019;Juselius, Møller, & Tarp, 2014;Musibau, Yusuf, & Gold, 2019) which does not account for cross sectional dependence. Ali, Yusop, Kaliappan, and Chin (2020) noted that these conventional technique produce biased estimate in the presence of cross sectional dependence.…”
Section: Introductionmentioning
confidence: 99%
“…We start our analysis to test the presence of unit root (data stationarity) of each variable in time series data. It is essential to test the order of the series or presence of unit root in the series in order to get an appropriate panel model (Musibau, Yusuf, & Gold, 2019). Whereas, there are several tests usually used for this purpose, such as Levin and Lin (1993), Hadri (2000), Levin, Lin and Chu (LLC) (2002) and Shin (1997, 2003).…”
Section: The Panel Unit Root Testmentioning
confidence: 99%
“…Thus, this paper used the most common tests such as Levin et al (LLC) (2002) and Shin (1997, 2003) as also considered the two recent unit root tests (Annala & Chen, 2011). According to Musibau et al (2019), the main hypothesis of panel unit root as established in LLC is as shown in equation 4. ∑…”
Section: The Panel Unit Root Testmentioning
confidence: 99%
“…We start our analysis to test the presence of unit root (data stationarity) of each variable in time series data. It is crucial to test the order of the series or presence of unit root in the series in order to get an appropriate panel model (Musibau, Yusuf, & Gold, 2019). Whereas, there are several tests usually used for this purpose, such as Levin and Lin (1993), Hadri (2000), Levin, Lin, and Chu (LLC) (2002) and Shin (1997, 2003).…”
Section: The Panel Unit Root Testmentioning
confidence: 99%